2017
DOI: 10.1111/coa.12947
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic sudden sensorineural hearing loss and ménière syndrome: The role of cerebral venous drainage

Abstract: Objectives: To evaluate the influence of cerebral venous drainage on the pathogenesis of idiopathic sudden sensorineural hearing loss (ISSHL) and M eni ere syndrome (MD).Design: Observational, prospective, cohort study. Results: No morphological alterations were found both in patients and controls.There were no signs of stenosis, blocked flow, membranes, etc. We found lower minimum, mean and maximum velocities in distal IJVs (P = .019; P = .013; P = .022; respectively) and left VVs (P = .027; P = .008; P = .0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…A study by Ciccone et al. of patients with idiopathic SSNHL revealed via ultrasound colour Doppler statistically significant reduced minimum, maximum, and mean velocities of the left internal jugular vein and left vertebral vein compared to controls, irrespective of the diseased ear (21). In this study, 11.8% of patients with idiopathic SSNHL compared to 9.7% of the control group ( P = 1.000) exhibited changes consistent with venous abnormalities (i.e.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A study by Ciccone et al. of patients with idiopathic SSNHL revealed via ultrasound colour Doppler statistically significant reduced minimum, maximum, and mean velocities of the left internal jugular vein and left vertebral vein compared to controls, irrespective of the diseased ear (21). In this study, 11.8% of patients with idiopathic SSNHL compared to 9.7% of the control group ( P = 1.000) exhibited changes consistent with venous abnormalities (i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, Ciccone et al. found an association between early markers of atherosclerosis and lower pure-tone averages on audiologic evaluation in patients diagnosed with idiopathic SSNHL (21). Our study found chronic microangiopathic disease in 25.7% of patients with idiopathic SSNHL, which was also found at an identical rate in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathophysiology of SSHL remains controversial, some asymmetric anatomical conditions may be responsible for the unilateral involvement of SSHL. Since the intracranial venous system is often asymmetric and cochlear venous insufficiency has been considered to be one of the causes of SSHL, we chose to focus our study on patients with SSHL to verify whether asymmetries of the intracranial venous drainage could play a role in the etiopathogenesis of SSHL 2,3,14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Ciccone et al have confirmed that the ISSHL patients were at a higher cardiovascular risk, which suggests the vascular genesis of cochlear damage. Moreover, asymmetrical alterations in venous extracranial hemodynamics could contribute to the pathogenesis of SSNHL [16]. Besides, they first mentioned that hearing thresholds of the contralateral ear were related to carotid intima-media thickness and flow-mediated dilation of the brachial artery representing subclinical atherosclerosis [13].…”
Section: Discussionmentioning
confidence: 99%